Аналіз схем повторного використання частот для мереж мобільного зв’язку 4-5G - Бабіч, М. Р.; Горбачов, В. О.; Москалець, М. В. (ХНУРЕ, 2025)
The application of effective frequency allocation schemes such as reuse-1, reuse-3, soft frequency reuse (SFR), partial frequency reuse (PFR), and soft fractional frequency reuse (SFFR) in the 4-5G mobile network planning methodology is analyzed. Frequency allocation models used for resource allocation for both macrocells and femtocells are proposed to ensure the coexistence of both networks and minimize interference to the greatest extent possible
Keywords: 4-5G; повторне використання частот